AN ECONOMIC STUDY FOR IRAQ'S RICE IMPORTS FOR THE PERIOD (1990-2015) and PREDICTION FOR THE PERIED (2016 – 2023) - & Al – Badri, AL - Karawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This research aims at predicting the imported quantities of rice in Iraq for the period 2016-2023 through the use of the self-regression model (VAR). The values ​​of explanatory variables (local production, population, national income, local price index, of rice consumption), where the predicted values ​​for each of these variables are estimated separately using the moving average method based on the data of the last 10 years. The research concluded that there is no difference between the actual values ​​and the predicted values ​​in the short term. This is the problem that emerged from the research which is the mismatch between these values. Therefore, the research recommended that the short term forecasts be adopted in the formulation of import policies, especially after the validity of the model To predict after testing the predictive power of the model.